2013
DOI: 10.4028/www.scientific.net/amm.467.49
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Activated Carbon Sorbents Based on Greek Walnut

Abstract: This article presents the results of the synthesis of carbon nanomaterials: Nanoscale materials obtained by carbonization of waste agricultural products (apricot kernel, Greek walnut (GW), rice husk). The results of physico-chemical characteristics of the obtained nanomaterials. Physico-chemical parameters of the synthesis of carbonized sorbents based on plant raw material are investigated along with the properties of these sorbents. The data of FTIR, ESR spectroscopy & BET-method, as well as electron micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 2 publications
0
7
0
2
Order By: Relevance
“…В настоящее время экономические причины и экологические проблемы привлекают значительное внимание исследователей к биомассе в качестве сырья для производства углеродных материалов. Так, в качестве прекурсора для получения активированного угля с большой площадью поверхности использовались древесина, листья, пивной осадок, рисовая шелуха и другие типы биомассы [4][5][6][7][8][9][10][11]. Активированные угли успешно получают из рисовой шелухи, карбонизированной в бескислородной атмосфере [12].…”
Section: Introductionunclassified
“…В настоящее время экономические причины и экологические проблемы привлекают значительное внимание исследователей к биомассе в качестве сырья для производства углеродных материалов. Так, в качестве прекурсора для получения активированного угля с большой площадью поверхности использовались древесина, листья, пивной осадок, рисовая шелуха и другие типы биомассы [4][5][6][7][8][9][10][11]. Активированные угли успешно получают из рисовой шелухи, карбонизированной в бескислородной атмосфере [12].…”
Section: Introductionunclassified
“…Clinical trials have shown that copper can minimize the bacterial and viral infections, while it can also be useful in preventing the spread of infectious illnesses [ 14 , 18 ]. However, the presence of an excessive amount of metal ions has harmful effects on human health and the environment [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…For CDI, the most promising materials for electrodes are those which have a high specific surface area, a large number of subnanometric pores, good electrical conductivity and low cost [13][14][15][16][17][18][19]. Due to these properties, nanoporous carbons have attracted the attention of researchers around the world [20][21][22].…”
Section: Introductionmentioning
confidence: 99%